2016
DOI: 10.1111/jan.13173
|View full text |Cite
|
Sign up to set email alerts
|

Should nurses be role models for healthy lifestyles? Results from a modified Delphi study

Abstract: The findings challenge the assumptions underpinning the argument that nurses be healthy role models. Further research is needed to understand the views of frontline nurses and to further explore avenues by which health services staff health can be improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 35 publications
1
34
0
1
Order By: Relevance
“…Nurses as health professionals may be expected to practice healthy lifestyles and be role models for health [3,50,51]. Nevertheless, the inconsistency in the literature about the mixed influence of knowledge on HPBs may be explained by the relationship between psychological factors, such as self-regulatory mechanisms, and behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses as health professionals may be expected to practice healthy lifestyles and be role models for health [3,50,51]. Nevertheless, the inconsistency in the literature about the mixed influence of knowledge on HPBs may be explained by the relationship between psychological factors, such as self-regulatory mechanisms, and behavior.…”
Section: Discussionmentioning
confidence: 99%
“…This pilot study tested whether a social marketing campaign that emphasized a professional expectation of nurses as credible public health messengers could encourage social conformity amongst nurses to demonstrate healthier lifestyles. Although there is little evidence that patients actually reject messages from staff who may be obese or smokers (Kelly, Wills, Sykes, ), it is an accepted assumption that healthcare staff should “practise what they preach” (Kelly, Wills, Jester, et al., ). Stage One of the present study showed that most nurses accepted this proposition (i.e., it was socially normative), even if they did not evidence a healthy lifestyle themselves.…”
Section: Discussionmentioning
confidence: 99%
“…There are limits to how far the concept was tested due to budgetary constraints and the nature of the campaign and its limited reach. Following from other work in this area (Kelly, Wills, Jester, et al, 2017;Kelly, Wills, Sykes, 2017) however, it does seem that there is a lack of acceptance that nurses should be role models and resistance to this concept being promoted as a realistic expectation of nurses.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with this, Kelly et al. () reported that it was crucial that nurses felt supported rather than punished or blamed.…”
Section: Discussionmentioning
confidence: 78%